The Effect of Realistic Mathematics Education Models using Fraction Cards on Improving Elementary School Students' Learning Outcomes in Fraction Multiplication - Hana Fauziyyah; Rinaldi Yusup; Samsul Pahmi (Jurnal Kiprah Pendidikan, 2026)
This research is motivated by the low learning outcomes of students in multiplication material. This study aims to determine the effect of the application of the Realistic Mathematics Education model assisted by fraction cards media on student learning outcomes in fraction multiplication material. The RME model was chosen because of the emphasis on contextual and meaningful learning through the connection of mathematical material with everyday life. The study used the Pre-Experiment method with a One Group Pretest-Posttest Design and involved 26 fourth-grade students of SDN Leuwiliang as samples. Data collection techniques used learning outcome tests and observations of student activities. The results showed an increase in student learning outcomes after the application of the RME model assisted by fraction cards, indicated by an average pretest score of 64.62 and a posttest score of 82.88. The results of the Paired Sample t-Test obtained a significance value of 0.001 <0.05, so there was a significant difference between learning outcomes before and after treatment. This finding is proven effective in improving student learning outcomes in fraction multiplication material in elementary schools